Control and Utilization of Immigrant Guildhalls: Examining the Layout Rules in Chengdu Prefecture During the Qing Dynasty - Wenbin Xiao; E Huang; Chaw Thiri Khaing; Huiqiao Yang; Heping Li (Buildings)
The immigrant guildhall was an important landscape element in the cities of Sichuan during the Qing Dynasty. This study explores the attribute characteristics, spatial distribution characteristics, and spatial layout rules of immigrant guildhalls by examining the Chengdu prefectural city during the Qing Dynasty as an example, using qualitative logical induction, GIS spatial analysis, and spatial syntax. The results show the following. (1) Immigrant guildhalls were civic buildings with a low level of support for the official regime. They had a grand scale, prominent building height, and unique architectural shape. (2) The layout rules for immigrant guildhalls included keeping immigrant guildhalls a certain distance from the dominant administrative, cultural, and educational facilities. Immigrant guildhalls had limited participation in the construction of the main axis of the city but partially participated in the construction of the secondary axis of the city. Immigrant guildhalls were mainly located in areas with well-developed businesses and convenient road transportation. (3) The official adopts two methods, control and utilization, to enable immigrant guildhalls to participate in the construction of the urban landscape order. These findings reveal the characteristics of the layout of immigrant guildhalls in the city during the Qing Dynasty and provide a basis for understanding the construction order of traditional Chinese cities.